Empathy cultivation through (pro)social media: a counter to compassion fatigue - Roberts, Jessica Stewart (2021)
While a sizable body of literature suggests that repeated exposure to images of suffering may provoke compassion fatigue and news avoidance in audiences, this paper examines whether a different kind of representation can allow viewers to connect with the subjects of media coverage, cultivating empathy for them. The hope is that understanding the emotional impact of the way people are represented in news stories will help journalists better serve the public’s need for what Schudson called “social empathy”, “stories that—often in a human-interest vein—inform citizens about neighbors and groups they may not know or understand” and create a space where audiences can express positive emotions about their fellow citizens. This paper considers the reactions of followers of the “Humans of New York” (HONY) social media feed to the subjects of the feed’s posts, who are not portrayed as tragic victims, but humanized through portrayals of commonplace concerns, such as family, career, and romantic relationships. Comments on more than 8000 HONY posts over a year were analyzed using the Linguistic Inquiry Word Count program. Results indicate that comments on HONY are overwhelmingly positive and socially oriented, suggesting that this type of representation may be effective in countering compassion fatigue and allowing for better social connection.